Pengaruh Pengungkapan Emisi Karbon, Kinerja Lingkungan, dan Ukuran Perusahaan terhadap Kinerja Keuangan (Studi Empiris pada Perusahaan Sektor Energy, Basic Materials, dan Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Periode 2020–2022) - Windari, Ranti (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study examines the effects of carbon-emission disclosure, environmental performance, and firm size on financial performance in energy, basic materials, and consumer non-cyclicals companies listed on the Indonesia Stock Exchange during the 2020–2022 period. The study employs a quantitative approach using secondary data obtained from annual reports and sustainability reports. The sample was selected through purposive sampling and consisted of 21 companies, resulting in 63 initial firm-year observations. After eliminating 15 outlier observations, 48 observations were included in the final analysis. Financial performance was measured using Return on Assets, carbon-emission disclosure was measured using an 18-item disclosure index based on the Carbon Disclosure Project framework, environmental performance was measured using PROPER ratings, and firm size was measured using the natural logarithm of total assets. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS version 27. The results show that carbon-emission disclosure has a positive and significant effect on financial performance. Environmental performance has a negative but insignificant effect, while firm size has a positive but insignificant effect. Simultaneously, carbon-emission disclosure, environmental performance, and firm size significantly affect financial performance. The adjusted coefficient of determination is 17.7%, indicating that the model explains 17.7% of the variation in financial performance.